Accounting concepts applications - Skousen, K. Fred; Albrecht, W.Steve; Stice, James D.; Stice, Earl K. (Cincinnati : South - Western College Publishing, 1999)
Business
Keywords: Accounting; Financial reporting; Investing; Management accounting; Decision making